2005
DOI: 10.1227/01.neu.0000163250.71951.18
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hemorrhage in Hemangioblastomas of the Central Nervous System

Abstract: The overall incidence of hemorrhage in patients with hemangioblastoma is low. An important indicator for the probability of hemorrhage is tumor size, as spontaneous or postoperative hemorrhage occurred exclusively in extraordinarily large tumors. Hemangioblastomas smaller than 1.5 cm (the vast majority of these tumors) harbor virtually no risk of spontaneous hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 20 publications
1
77
1
1
Order By: Relevance
“…6) Although spontaneous hemorrhage is a very uncommon event in the natural history of HB, 4,6,13) uncontrollable intraoperative hemorrhage sometimes occurs. Endovascular embolization of the feeding artery and subsequent operative resection are the recommended procedures, because preoperative embolization can control the arterial supply and reduce tumor vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…6) Although spontaneous hemorrhage is a very uncommon event in the natural history of HB, 4,6,13) uncontrollable intraoperative hemorrhage sometimes occurs. Endovascular embolization of the feeding artery and subsequent operative resection are the recommended procedures, because preoperative embolization can control the arterial supply and reduce tumor vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when performing embolization with solid embolization materials, uneven intra-tumor embolization related to the large capillary floors of cerebellar hemangioblastomas may lead to an imbalance in the intra-tumor capillary floor pressure, causing intra-tumor hemorrhage. 9) On the other hand, a study reported that the incidence of hemorrhagic complications after embolization with liquid embolization materials was lower than after embolization with granular embolization materials. 10) In this study, prior to tumor resection of cerebellar hemangioblastomas, we performed embolization using the plug and push technique after diluting NBCA with oily contrast medium so that its adhesiveness may be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…16) Only 17 cases of hemangioblastoma associated with SAH have been reported 2,3,5,6,8,9,13,16,18,20,21,27,29) (Table 1). The characteristic symptoms of spinal SAH are severe pain along the spinal axis (neck pain and back pain/lumbago), radicular pain, paresis originating at the spinal roots, 16) or myelopathy, as seen in our present patient.…”
Section: Discussionmentioning
confidence: 99%